Forecasting The Stock Price Movement of Bank Aladin Syariah Using The Arima Model: A Study on Indonesia’s First Islamic Digital Bank - Handayani, Disfa Lidian (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2025)
This study models the stock price movement of Bank Aladin Syariah (BANK), Indonesia’s first Islamic digital bank, using the ARIMA method. As a pioneer in branchless, technology-driven sharia banking, Bank Aladin significantly contributes to enhancing financial inclusion and advancing Islamic finance. Its status as a first mover renders it particularly relevant to investors and market analysts, as its stock performance reflects broader sentiment toward technological adoption in the Islamic financial sector. The dataset comprises 694 daily closing prices sourced from Yahoo Finance, spanning the period from May 18, 2022, to March 27, 2025. Given the non-stationary nature of the data, first-order differencing was applied to attain stationarity. The ARIMA(1,1,1) model was identified as the most appropriate, producing nine-step-ahead forecasts ranging from 804.9910 to 804.9836 with gradually increasing standard errors. The model yields stable and conservative projections, offering valuable insights for investors and stakeholders in the Islamic digital banking sector.